Missions that changed the war [videorecording (DVD)] : the Doolittle raid - Tennyson, Jon; Guyette, Scott; Sinise, Gary (Acorn Media, 2012)
Outraged at the attack on Pearl Harbor, President Franklin Roosevelt ordered his military leaders to find a way to hit back at an enemy whose homeland was beyond the reach of U.S. warplanes. The result was a daring plan to load B-25 bombers on an aircraft carrier, sail within range of Japan, bomb its cities, and then fly on to the safety of China. Only one man was considered up to the task of leading the mission: Lieutenant Colonel James H. Doolittle.